2002
DOI: 10.1142/s108842460200018x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and spectroscopic characterization of Ni, Zn, Pd and Pt tetra(pentafluorophenyl)porpholactone with comparisons to Mg, Zn, Y, Pd and Pt metal complexes of tetra(pentafluorophenyl)porphine

Abstract: Ni , Zn , Pd and Pt tetra(pentafluorophenyl)porpholactone (TFPL) were synthesized and identified by their optical and mass spectra. The lactone ring was produced from the parent free-base porphyrin using silver nitrate and oxalic acid with a yield of 73%, and the metals were inserted by standard procedures from metal salts. The compounds show intense Soret Bands in the region 390-420 nm. The longest wavelength visible absorbance peaks, in the region 572-608 nm, are weaker than the Soret peaks by a factor of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 12 publications
5
67
0
Order By: Relevance
“…[1][2][3][4] Most oxygen sensors employ such widespread indicators as ruthenium(II) polypyridyl complexes, [5][6][7] platinum(II) and palladium(II) porphyrins [8][9][10][11] and their analogues. [12][13][14] Other luminescent indicators are less popular which is explained by their inferior photophysical properties (low absorption coefficients and luminescence quantum yields, short luminescence decay times, poor photostability etc.) [3]or by complicated multistep synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Most oxygen sensors employ such widespread indicators as ruthenium(II) polypyridyl complexes, [5][6][7] platinum(II) and palladium(II) porphyrins [8][9][10][11] and their analogues. [12][13][14] Other luminescent indicators are less popular which is explained by their inferior photophysical properties (low absorption coefficients and luminescence quantum yields, short luminescence decay times, poor photostability etc.) [3]or by complicated multistep synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The quenching of the photo-excited triplet state of Pt(II) complexes of porphyrins is the origin of their utility in pressure-sensitive paints (PSP) that allow for the continuous mapping of surface pressures [12][13][14][15][16]. We have found that the use of the fluorinated ligand T F PP in PSP formulations increases the phosphorescence lifetime of the paints and leads to photo-stable coatings, presumably because of the protection the pentafluorophenyl groups provide from singletoxygen-mediated oxidative degradation of the chromophore [13][14][15][16]. Further, T F PP was suggested as a chemically inert and strongly light-absorbing matrix in MALDI-TOF mass spectrometry [17].…”
mentioning
confidence: 99%
“…These side reactions may also give other by-products during metalation of porphyrins in DMF. It is also noted that electron-withdrawing groups attached to the porphyrin periphery also promote the formation of other (Lai et al 2004;Khalil et al 2002). Recently, it was argued that microwave-assisted methods might be less beneficial for the metalloporphyrin synthesis because of some limitations of the traditional solvents (Dean et al 2008).…”
Section: Resultsmentioning
confidence: 99%